Review ON THE MONOGRAPH OF D. A. LYAPINA "RITUALS OF POWER: ESSAYS ON THE SOCIO-POLITICAL HISTORY OF RUSSIA THE EARLY MODERN PERIOD" - Yu. V. Stepanova (Современная наука и инновации, 2022)
The book covers a wide range of issues related to the history of the XVII century., which has been further coverage in several articles of the author. The monograph also has a political dimension, since one of the Central concepts here is the notion of «power».